Viktor Denisenko’s Novel The Vilnius Apocalypse (2022) in the Context of the Christian Apocalyptic Tradition - Burov, Aleksej; Ickovič-Zenovič, Diana (Literatūra, 2025)
This article focuses on Viktor Denisenko’s novel The Vilnius Apocalypse, published in 2022. It aims to examine the relationship between the novel’s plot and the Christian apocalyptic tradition, which gained its form in the High Middle Ages. To achieve this, a comparative analysis of the apocalyptic motifs and figures found in the narrative is carried out. The study suggests that the author makes extensive use of the elements of the Christian apocalyptic narrative, which undergo a transformation in the process of reception in terms of both form and content. The depiction of the end of the world in the novel does not reveal the transcendental aspect of apocalyptic thinking. Instead, in the narrative scenario the apocalypse is equated with a crisis and a large-scale catastrophe. The article concludes that the plot of The Vilnius Apocalypse cannot be considered as part of the Christian apocalyptic tradition.